Pemberdayaan Masyarakat melalui Hidroponik dan Penguatan Literasi Keuangan UMKM Hijau di Kawasan Padat Penduduk dan Rawan Banjir Kedaung Kali Angke, Jakarta Barat - Rina Yuliastuty Asmara; Dudi Permana; Anwar Allah Pitchay (Universitas 17 Agustus 1945 Jakarta, 2026)
Communities living in densely populated urban areas often face challenges related to food availability, limited land, and unstable household income. In Kedaung Kali Angke, West Jakarta, many residents rely on informal economic activities and small household businesses, while opportunities for productive urban farming and sustainable business development remain underutilized. Financial management skills among community members are also relatively low, particularly in bookkeeping, budgeting, and business planning. This international joint community service program, carried out through a collaboration between Universitas Mercu Buana and Universiti Sains Malaysia, addressed these conditions through an integrated empowerment approach combining hydroponic cultivation and financial literacy education. The activity was implemented on 24 April 2026 in Kedaung Kali Angke Sub-District, West Jakarta, and was attended by 75 participants. Sessions covered accounting education for entrepreneurs, hydroponic awareness, hands-on practice in urban agriculture systems, and open discussion. Evaluation results showed an overall community-service assessment index of 87.0% (Very Good category) and a participant satisfaction level of 92.7% (Satisfied to Very Satisfied), with an average conformity level between expectation and performance of 99.3%. The program is expected to strengthen household food security, improve financial literacy, and encourage the development of environmentally friendly green MSMEs, and supports Sustainable Development Goals 1, 2, 8, 11, and 12.